2021
DOI: 10.3389/fpls.2021.736212
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Morphogenesis: Insights From the Moss Physcomitrium patens

Abstract: Specialized photosynthetic organs have appeared several times independently during the evolution of land plants. Phyllids, the leaf-like organs of bryophytes such as mosses or leafy liverworts, display a simple morphology, with a small number of cells and cell types and lack typical vascular tissue which contrasts greatly with flowering plants. Despite this, the leaf structures of these two plant types share many morphological characteristics. In this review, we summarize the current understanding of leaf morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…There are no non-conventional types of monolignol structure detected in PpCAD1 _OE gametophores. Despite lignin-like polymers considered B-ring flavonoids similar to H-, G-, and S- lignin units in moss as UV screens, it is believed that the enhanced lignin-like polymers might be intermediate in the lignin biosynthetic pathway [ 25 ]. Furthermore, three pieces of evidence support that lignin-like molecules are enhanced in P. patens .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no non-conventional types of monolignol structure detected in PpCAD1 _OE gametophores. Despite lignin-like polymers considered B-ring flavonoids similar to H-, G-, and S- lignin units in moss as UV screens, it is believed that the enhanced lignin-like polymers might be intermediate in the lignin biosynthetic pathway [ 25 ]. Furthermore, three pieces of evidence support that lignin-like molecules are enhanced in P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. patens has a simple developmental life cycle with a predominant haploid phase, which dramatically facilitates genetic analysis [24]. In addition, phyllids, rhizoids, and protonemal filaments of P. patens consist of only one cell layer, making easy observation using microscopic analysis [25]. Even though the existence of lignin in moss is still controversial, P. patens has all the core lignin biosynthetic genes without ferulate 5-hydroxylase (F5H) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The moss Physcomitrium patens ( P. patens ) is a useful material for observing cellular growth due to its simple organ structures, such as phyllids (hereafter, leaves) with a single cell layer (Kofuji & Hasebe, 2014; Medina et al ., 2019; Lin et al ., 2021). Our analysis of the deletion mutant of the ABCB14 ortholog in P. patens revealed that mutant leaf cells lost regular anisotropic expansion, resulting in shrunken leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In Physcomitrium patens (formerly known as Physcomitrella patens), midribs contain hydroid and stereid cells. Hydroids are thin-walled cells that are initially live, then undergo programmed cell death, and have a totally degenerated protoplasm upon maturation (5)(6)(7)(8). By contrast, stereids have thickened cell walls and mainly serve the purpose of support (8).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, some species of nonvascular mosses, as one of the earliest land plants, have evolved midribs in phyllids (hereafter called leaves) for water conduction and support ( 5 , 6 ). Despite the similarity in function, midribs are drastically different from, and much less branched than, the vasculature ( 5 , 7 , 8 ); therefore, the water transport efficiency of midribs is low and moss mainly relies on capillarity to externally transport water ( 6 , 8 ). In Physcomitrium patens (formerly known as Physcomitrella patens ), midribs contain hydroid and stereid cells.…”
Section: Introductionmentioning
confidence: 99%